Best Practice Teacher Competency Development In State Elementary Schools In Angrek District North Gorontalo District - Imran, Ulfa Hiku; Mas, Sitti Roskina; Lamatenggo, Nina (Faculty of Education Universitas Negeri Malang, 2023)
This study aims to analyze best practice development of teacher pedagogical competence, teacher professional competence, teacher social competence, and teacher personality competence in public elementary schools in Anggrek District, North Gorontalo Regency. The research method used is explanatory. The data collection technique is by distributing questionnaires to the respondents. The sample in this study was 101 teachers (N=134). The data analysis used is descriptive quantitative analysis. The results of this study indicate that best Practice teacher pedagogic competency development has a score of 85.26% which is in the Good category. Teacher professional competence development scores 82.30%, which is in the Good category. Teacher social competency development scores 83.07%, which is in the good category. Teacher personality competency development scores 85.46%, which is in the good category.